2023
DOI: 10.1039/d3sc00332a
|View full text |Cite
|
Sign up to set email alerts
|

The expedient, CAET-assisted synthesis of dual-monoubiquitinated histone H3 enables evaluation of its interaction with DNMT1

Abstract: Site-selective conjugation chemistry has proved effective to synthesize homogenously ubiquitinated histones. Recently, a powerful strategy using 2-((2-chloroethyl) amino) ethane-1-thiol (CAET) as a bifunctional handle was developed to generate chemically stable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…The recent cell biology findings show that histones can be simultaneously monoubiquitylated at multiple lysine residues. A representative example is H3 ubiquitylation at the adjacent lysines (positions 14, 18, and 23) catalyzed by the E3 ligase Uhrf1, which is essential for the functions of the maintenance DNA methyltransferase DNMT1. , We and others recently revealed that H3 dual monoubiquitylation at K18 and K23 can directly interact with and activate DNMT1, ,, but the consequences of other H3 ubiquitylation patterns on this process are still unclear. For example, the binding affinity of DNMT1 with other dual-monoubiquitylated H3 proteins (K14- and K18- or K14- and K23-dual-monoubiquitylated one) or triple-monoubiquitylated H3 has not been evaluated yet, which is highly dependent on the access of site-specifically ubiquitylated H3 proteins.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The recent cell biology findings show that histones can be simultaneously monoubiquitylated at multiple lysine residues. A representative example is H3 ubiquitylation at the adjacent lysines (positions 14, 18, and 23) catalyzed by the E3 ligase Uhrf1, which is essential for the functions of the maintenance DNA methyltransferase DNMT1. , We and others recently revealed that H3 dual monoubiquitylation at K18 and K23 can directly interact with and activate DNMT1, ,, but the consequences of other H3 ubiquitylation patterns on this process are still unclear. For example, the binding affinity of DNMT1 with other dual-monoubiquitylated H3 proteins (K14- and K18- or K14- and K23-dual-monoubiquitylated one) or triple-monoubiquitylated H3 has not been evaluated yet, which is highly dependent on the access of site-specifically ubiquitylated H3 proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the increase in potential byproducts and steric hindrance might make the synthesis of multi-monoubiquitylated histones more challenging, and their synthesis has not been reported yet. Actually, our recently reported method that was developed to generate the H3K18UbK23Ub analogue was difficult in the preparation of H3Ub3 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations